Description of last-instar larva of Corydalus nubilus Erichson, 1848 (Megaloptera: Corydalidae) and notes on its bionomics - de Azevêdo, Carlos A.s.; Hamada, Neusa (Zootaxa, 2006)
Corydalus nubilus Erichson, 1848 (Megaloptera: Corydalidae) is a dobsonfly species with Amazonian distribution. Only its adult stage is known. In this study we provide the first description of the last-instar larva of this species and notes on the bionomics of the larvae and adults.